Energetic considerations in cross-country skiing - Herzog, W.; Killick, A.; Boldt, K. R. (Sports Performance, 2015)
Cross-country skiing is a four-legged gait, and some gait patterns, such as 2-skate skiing, are similar to those adopted by animals (galloping horse). Four-legged animals change gait patterns with increasing speeds of locomotion, at least in part, to minimize metabolic energy expenditure. For example, a horse will switch from a walk, to a trot, and finally to a gallop as speed of locomotion increases. Similarly, skate cross-country skiers will switch from a 2-skate gait to a 1-skate gait with increasing speeds of locomotion, but then unlike any other animal, will revert back to the previously rejected 2-skate gait pattern at very high speeds. We used oxygen uptake measurements, force measurements in poles and skis, 3-dimensional movement analysis and functional muscle properties to explain this result. We found that propulsion in 1-skate skiing comes primarily from the arms/poles, while propulsion comes primarily from the legs/skis in the 2-skate technique. We also found that ground contact times for the skis are virtually independent of the skiing speed while pole contact times decrease dramatically with increasing speeds. Furthermore, propulsive forces from the arms dropped from skiing at 15 km/h to skiing at 30 km/h while simultaneously requiring much more metabolic energy. Finally, the cost of transport curves for 1-skate and 2-skate skiing intersected twice, indicating better efficiency for the 2-skate technique at slow and very fast speeds, and better efficiency for the 1-skate technique at intermediate to fast speeds. Combined, these results suggest that arm/pole action is optimized at intermediate speeds, thereby providing an advantage to the 1-skate technique which relies primarily on arm propulsion, while arm/pole action is highly inefficient at very high speeds, thus switching to the 2-skate technique which relies primarily on leg propulsion, is good strategy.